3D Printing and Smart Farming: Transforming Food Processing and Post-Harvest Technology - Kanica Roy; Rohit Dutta Choudhury; Joytu Debnath (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
One of the greatest revolutions in food processing and agriculture has been the combination of 3D printing and smart agricultural technology in response to the urgent demands for waste reduction, sustainability, and food security. It covers how innovative technologies in modern agriculture can be used-from their perspective in precision farming, custom food production, sustainable resource management, to post-harvest technology. This is because IoT, AI, and additive manufacturing power provide real-time monitoring of environmental parameters for optimizing crop health management and resource use and open up opportunities for customization of food products through 3D printed customized food products, biodegradable packaging, and on-demand equipment manufacturing. These regions would face huge up-front costs, little technological know-how, many regulatory constrictions, and also severe infrastructure deficiencies in applying and adopting the two technologies, respectively. Future work or research regarding the above two technologies needs to come from cost efficiencies, policymaking, scalability, as well as no faults to enable both full potentials for proper, effective working. This paper will conclude by mentioning that even so, there will remain a pressing need for more advanced forms of interdisciplinary cooperation as well as public education in order to achieve the maximum benefits of such technologies towards attaining a more resilient and sustainable global food system.